2017
DOI: 10.1186/s40100-017-0075-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of agricultural cooperatives membership on the wellbeing of smallholder farmers: empirical evidence from eastern Ethiopia

Abstract: This study evaluated the impact of agricultural cooperative membership on the wellbeing of smallholder farmers using cross-sectional data collected from the eastern part of Ethiopia. Using consumption per adult equivalent as a wellbeing indicator, we measured the impact of agricultural cooperative membership by implementing propensity score matching and endogenous switching regression estimation techniques. Both estimation methods indicate that joining agricultural cooperatives has a positive impact on the wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 57 publications
(86 reference statements)
10
83
1
1
Order By: Relevance
“…The study indicated a treatment effect of 17.6–26.5 per cent on consumption expenditure. However, like Verhofstadt and Maertens () and Shumeta and D'Haese (), Ahmed and Mesfin () also observed the treatment effect increased as farm size increased. To add further ambiguity, Mojo et al () observed a positive impact of membership in Ethiopian coffee cooperatives on farm income with switching regression but not with propensity score matching.…”
Section: Performancementioning
confidence: 79%
See 1 more Smart Citation
“…The study indicated a treatment effect of 17.6–26.5 per cent on consumption expenditure. However, like Verhofstadt and Maertens () and Shumeta and D'Haese (), Ahmed and Mesfin () also observed the treatment effect increased as farm size increased. To add further ambiguity, Mojo et al () observed a positive impact of membership in Ethiopian coffee cooperatives on farm income with switching regression but not with propensity score matching.…”
Section: Performancementioning
confidence: 79%
“…(), Ma and Abdulai () observed a stronger effect of cooperative membership for relatively small members (5.73%) than relatively large members (3.81%). Finally, also using switching regression, Ahmed and Mesfin () studied a sample of 250 farm producers in Ethiopia and took consumption expenditure per adult as the outcome variable. The study indicated a treatment effect of 17.6–26.5 per cent on consumption expenditure.…”
Section: Performancementioning
confidence: 99%
“…These variables include age, education, dependency ratio, farm size, sprayer ownership, computer ownership, income specialization, marketing contract, labor availability, risk attitude, social networks, and location variables. The choice of these explanatory variables is primarily based on previous studies on cooperative membership (e.g., Ahmed & Mesfin, ; Bernard & Spielman, ; Chagwiza et al., ; Fischer & Qaim, ; Ito et al., ; Mojo et al., ; Wossen et al., ; Zheng et al., ).…”
Section: Econometric Approachmentioning
confidence: 99%
“…Government programs have thus emerged to enhance smallholder farmers’ performance in modern agricultural production. Among others, agricultural cooperatives have been promoted based on their strong potential to improve smallholders’ farm performance (Ahmed & Mesfin, ; Chagwiza, Muradian, & Ruben, ; Francesconi & Wouterse, ; Hellin, Lundy, & Meijer, ; Liang, Hendrikse, Huang, & Xu, ; Mojo, Fischer, & Degefa, ). Generally, the development of cooperative organization in developing countries is expected to facilitate smallholder farmers’ market participation, increase farm incomes, enhance crop productivity, and lower production costs (Abebaw & Haile, ; Hellin et al., ; Huang & Ding, ; Mojo et al., ; Zheng, Wang, & Awokuse, ).…”
Section: Introductionmentioning
confidence: 99%
“…Study conducted by some researchers show that there is positive relationship between household heads, educated members, more land and few family size. According to Ahmed & Mesfin (2017), cooperative membership was found to be more beneficial for household heads with higher education, more land and fewer children.…”
Section: Results Interpretation and Discussion 41 Socio-economic Prmentioning
confidence: 99%